A decolonial reading of the 1840 English-Setswana Gospel of Luke with specific reference to Luke 1:59 and Luke 2:21 from the perspective of the damnés - Mothoagae, Itumeleng D. (HTS teologiese studies, 2021)
In their missionary endeavour the missionary societies such as London Missionary Society, did not only engage in public preaching but their public preaching took the form of a biblical discourse. They engaged with their audiences in a dialectical manner with the aim of converting them. In order to do that they had to question the religio-cultural practices of their audiences. The practices that the audiences engaged in were either public or private. This article analyses the public discourse about male and female initiations that took place in the public spaces and found their way into a newspaper named Mahoko a Becwana. The biblical discourse was amongst the missionaries: the converted and the traditional Batswana. It also focuses on Luke 1:59 and Luke 2:21 as translated by Robert Moffat. It is argued that the symbol thupiso is transmuted into bogwera. It is further argued that in his translation he engages in biblical discourse thus distorting the cultural meaning.Contribution: The article contributes to the biblical discourse within biblical sciences scholarship. It aims to contribute to the continual debates on the excavating and levelling of the epistemological voices that have been suppressed through colonial epistemological universalisation of knowledge from the perspective of the damnés.